ChemInform Abstract: The [U2(μ‐S2)2Cl8]4‐ Anion: Synthesis and Characterization of the Uranium Double Salt Cs5 [U2(μ‐S2)2Cl8]I. Issue 22 (15th May 2015) - Ward, Matthew D.; Pozzi, Eric A.; Lee, Minseong; Van Duyne, Richard P.; Choi, Eun Sang; Ibers, James A.
Abstract: Single crystals of Cs5 [U2 (μ‐S2 )2 Cl8 ]I are obtained by solid state reaction of U, GeI2 or SnI4, S, and CsCl as flux in a 1:1:3:3.5 molar ratio (C‐coated evacuated silica tubes, complex heating and cooling schedule, 75 wt% yield).